Polyhydroxylated fullerene nanoparticles attenuate brain infarction and oxidative stress in rat model of ischemic stroke - Rasouli Vani, Javad; Mohammadi, Mohammad Taghi; Sarami Foroshani, Mahsa Sarami; Jafari, Mahvash (Technische Universität Dortmund, 2016)
Oxidative stress is the common underlying mechanism of damage in ischemic stroke. Therefore, we aimed to evaluate the possible protective effects of polyhydroxylated fullerene derivatives on brain infarction and oxidative/nitrosative stress in a rat model of ischemic stroke. The experiment was performed by four groups of rats (each; n=12); Sham, Control ischemia, and ischemic treatment groups (Pretreatment and Posttreatment). Brain ischemia was induced by 90 min middle cerebral artery occlusion (MCAO) followed by 24 hours reperfusion. Rats received fullerene nanoparticles at dose of 1 mg/kg 30 min before MCAO and immediately after beginning of reperfusion. Infarct volume, contents of malondialdehyde (MDA), glutathione (GSH) and nitrate as well as superoxide dismutase (SOD) activity were assessed 24 hours after termination of MCAO. Brain infarct volume was 310 ± 21 mm3 in control group. Administration of fullerene nanoparticles before and after MCAO significantly decreased the infarct volume by 53 % (145 ± 45 mm3) and 81 % (59 ± 13 mm3), respectively. Ischemia also enhanced MDA and nitrate contents of ischemic hemispheres by 45 % and 25 % , respectively. Fullerene nanoparticles considerably reduced the MDA and nitrate contents of ischemic hemispheres before MCAO by 58 % and 17 % , respectively, and after MCAO by 38 % and 21 % , respectively. Induction of MCAO significantly decreased GSH content (19 % ) and SOD activity (52 % ) of ischemic hemispheres, whereas fullerene nanoparticles increased the GSH content and SOD activity of ischemic hemispheres by 19 % and 52 % before MCAO, respectively, and 21 % and 55 % after MCAO, respectively. Our findings indicate that fullerene nanoparticles, as a potent scavenger of free radicals, protect the brain cells against ischemia/reperfusion injury and inhibit brain oxidative/nitrosative damage.
EXCLI Journal;Vol. 15, 2016
Keywords: Ischemic stroke; oxidative damage; nitrosative damage; fullerene nanoparticles; 610